The Macroeconomic (and Distributional) Effects of Public Investment in Developing Economies - Furceri, Davide (IMF Working Papers; Working Paper ;, 2017)
This paper provides new empirical evidence of the macroeconomic effects of public investment in developing economies. Using public investment forecast errors to identify unanticipated changes in public investment, the paper finds that increased public investment raises output in the short and medium term, with an average short-term fiscal multiplier of about 0.2. We find some evidence that the effects are larger: (i) during periods of slack; (ii) in economies operating with fixed exchange rate regimes; (iii) in more closed economies; (iv) in countries with lower public debt; and (v) in countries with higher investment efficiency. Finally, we show that increases in public investment tend to lower income inequality.